추출조건에 따른 고구마 잎의 Lutein, β-Carotene 및 Polyphenol 함량 - Li Meishan; 장귀영(Gwi Yeong Jang); 이상훈(Sang Hoon Lee); 황세구(Se Gu Hwang); 신현만(Hyun Man Sin); 김홍식(Hong Sig Kim); 이준수(Junsoo Lee); 정헌상(Heon Sang Jeong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
This study was carried out to determine the simultaneous extraction conditions of functional components (lutein, ${β}$-carotene, total polyphenol, flavonoids, and phenolic compounds) from sweet potato leaves and to evaluate the antioxidant activities. Extraction conditions included different ethanol concentrations (1st extraction: 99.9% ethanol; 2nd extraction: 50~90% ethanol) and times (30, 60, and 90 min). The highest values of lutein and ${β}$-carotene content were obtained by the 2nd extraction at an ethanol concentration of 90%. The extraction yields of lutein and ${β}$-carotene decreased with increasing extraction time. The maximum polyphenol, flavonoid, and total phenolic acid contents and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activities were 32.3 mg gallic acid equivalent/g, 17.0 mg catechin equivalent/g, 2,842.6 mg/100 g, 17.0 mg ascorbic acid equivalent/g, and 1.94 mg/mL ($IC_{50}$) at the 2nd extraction with an ethanol concentration of 60%. The optimum extraction conditions were as follows; ethanol concentrations of the extraction solvent were 99.9% (1st extraction) and 60% (2nd extraction), and extraction time was 30 min. 본 연구는 고구마 잎에 함유된 carotenoids류인 lutein, ${β}$-carotene과 항산화 성분을 효과적으로 동시에 추출할 수 있는 방법을 연구하고 각 추출물에 대한 항산화 효과를 평가하였다. 1차 추출은 99.9% 에탄올을 사용하였고 2차 추출은 에탄올 농도를 50~90%로 증가시키며 추출하였다. Lutein과 ${β}$-carotene은 2차 추출 에탄올 농도 90%에서 각각 77.9% 및 68.5%로 가장 높은 추출률을 나타내었고 추출시간이 길어짐에 따라 감소하였다. Polyphenol, flavonoid 및 DPPH, ABTS 라디칼 소거능은 2차 추출 에탄올 농도 60%에서 각각 32.3 mg gallic acid equivalent/g, 17.0 mg catechin equivalent/g 및 1.94 mg/mL(EDA, $IC_{50}$), 17.0 mg AA eq/g(AEAC)으로 가장 높게 나타났으며, 추출시간이 길어짐에 따라 감소하였다. 또한, 총 페놀산 함량은 2차 추출을 에탄올 60~70%에서 추출 시 가장 높은 함량을 나타내었다. 지용성 물질인 carotenoids뿐만 아니라 대량으로 존재하는 수용성 물질인 페놀류를 동시에 추출하기 위해서는 99.9%의 에탄올을 사용하여 1차 추출을 하고, 60% 정도의 에탄올로 2차 추출을 30분 동안 추출 시 높은 추출률을 나타내어 루테인, 베타카로틴 및 폴리페놀 동시 추출법으로 가장 적합할 것으로 판단되었다.